Web-based interface system for bedside monitor - Kho, Yeh Yiian (2005)
From face-to-face consultation to medicine at a distance, technology is changing the way medical services are delivered to the people. We are going into an era where the information is being digitized to be stored in a database. This is done in order to reduce information overlap and redundancy that are the main problems the health care sector are facing right now. More hospitals in other more advanced countries are going paperless. In order to provide better services to the critically ill patients in the ICU or CCU, a data acquisition program is developed for the acquisition of vital signs monitored in the critical care units. This work discusses the work done in extracting the data and signal from patient monitor BSM 8800 to the computer. The data are acquired using RS232C Interface Protocol. The vital signs acquired include oxygen saturation (SaCh), heart rate (HR), electrocardiograph (ECG) signal, non-invasive blood pressure (NIBP), respiration rate (RR), temperature (TEMP) and end tidal carbon dioxide (PETCO2 or ETCO2). Ventricular Premature Contraction (VPC), ST level and arrhythmia information are also acquired and displayed to provide a more thorough information on the condition of the patients. Alarm detection is also programmed so that in critical conditions the vital signs will be displayed in red for extra caution. An ECG user control is designed and embedded in the web page in order to convert and plot the ECG waveform from hexadecimal values sent from the bedside monitor. The user control has been tested its accuracy and proved its validity to reconstruct the original ECG waveform. Basic patient information can also be seen from the graphical user interface (GUI) that has been developed. Physicians and medical practitioners have to register with the system before gaining access to the system and only the physician-in-charge of the patient can see the more intricate details of the patient.